Geochemical features of Sakhalin Island mud volcanoes - B., Shakirov R.; V., Sorochinskaja A.; S., Syrbu N.; B., Tsoy I.; Hoang, Nguyen; Anh, Le Duc (Vietnam Journal of Earth Sciences, 2018)
The study, based on a complex geochemical research, found that the composition of the most chemical elements in mud breccia from the Yuzhno-Sakhalinsky (YSMV) and Pugachevsky (PMV) mud volcanoes (Sakhalin Island), the unique phenomena of endogenous defluidization in the Hokkaido-Sakhalin fold system (alpine-type folding), are comparable to Clark (C) contents of these elements (0.8-1.2 ×C). For Na, Li, Zn andSn, the ratio between the elemental contentsand their Clarke values (Csample/Clark value) vary from 1.4 to 5.2 xC. But the increased contents of Na and Li are due to the ascending endogenous fluid revealed. Study of the mud breccia chemical composition changes in different explosive activity of YSMV under the seismic activity variationsallowed to establish that, when the mud-volcanic gryphonsare activated against the background of increase in the temperature of the water-mud mixture and the emission of spontaneous gases, the contents of a number of elements (iron, calcium, manganese, rare earth elements, etc.) are decreased. This is explained by the formation of soluble hydrocarbonate complexes. Daginskiegasgeothermal system (DGHS) trace elements depletedooze samples were compared with YSMV and PMVsamples and exposedthat thehigh ratios of Csample /Clarke values for the majority of elements do not exceed 0.6 × C.Ooze samples from DGHS having higher elemental contents than Clark contents were observed only for Cd content (2.2-3.4 ×C) and Pb (0.7-1.5 ×C). Analysis of diatom flora on the DGHS site indicates the existence of an active fluid dynamic system that drains oil and gas bearing complexes. The factors determining the "weighting" of the methane carbon isotope composition in the southern part of Sakhalin Island are the increased seismic activity of deep-seated faults, as well as the presence of intrusions (diabase) and metamorphically altered rocks. References Aliyev A.A., Guliyev I.S., Rakhmanov R.R., 2009. Catalog of eruptions of Azerbaijan mud volcanoes (1810-2007). Baku Nafta-Press, 109p. Astakhov A.S., et al., 2002. Defluitization process dynamic of the Central Sakhalin fault at seismic activization (by monitoring results of the Yuzhno-Sakhalinsky mud volcano in July - August 2001) DAN 2002, 386(2), 223-228. Decisions of operational interdepartmental regional stratigraphical meetings on the Paleogene and Neogene of east regions of Russia-Kamchatka, Koryak Upland, Sakhalin and Kuril Islands, 1998. An explanatory note to stratigraphical schemes. Responsible editor Gladenkov Y.B. Moscow GEOS, 147p. Diatomic algae of the USSR (fossil and modern), 1974. Leningrad Nauka, 1(1), 404p. Dubinin A.V., 2006. Geochemistry of rare-earth elements in the ocean. Moscow Nauka, 360p. Ershov V.V., Shakirov R.B., Obzhirov A.I., 2011. Isotope and geochemical characteristics of the Yuzhno-Sakhalinsky mud volcano free gases and their connection with regional seismicity. DAN, 440(2), 256-261. Fedorov Y.N., et al., 2012. Crude oil microelement characteristic of Vogulkinsky and Tyumen basins oil and gas area: comparison. Lithosphere, 2, 141-151. Geology of the USSR, 33. Sakhalin Island/Under the edited by Sidorenko A.V. Moscow Nedra, 1970, 464p. Grigoriev N. A., 2008. About clark content of chemical elements in the top part of continental crust. Lithosphere 1, 61-71. Thesis: 11.00.00. Yuzhno-Sakhalinsk, IMGG FEB RAS, 244p. Hasle G.R., Syvertsen E.E., 1996. Marine diatoms. Identifying Marine Phytoplankton. San Diego, Academic Press, 5-385. Horita J., 2001. Carbon isotope exchange in the system CO2-CH4 at elevated temperatures. Geochimica et Cosmochimca Acta, 65, 1907-1919. Kholodov V.N., 2002. Mud volcanoes: distribution regularities and genesis. Lithology and Mineral Resources, 3, 227-22001.41. Kopf A.J., 2002. Significance of mud volcanism. Rev. Geophys, 40(2), 2-1-2-52. Liu Chia-Chuan, et al., 2013. The geochemical characteristics of the mud liquids in the Wushanting and Hsiaokunshui Mud Volcano region in southern Taiwan: Implications of humic substances for binding and mobilization of arsenic. Journal of Geochemical Exploration, 128, 62-71. Lobodenko I.Y., 2010. Holocenic tectonic deformations (paleoseismodislocations) in zones of the Hokkaido-Sakhalin and Central Sakhalin faults. Candidate of geological and mineralogical science thesis. Moscow, 22p. Melnikov O.A., 1987. Structure and geodynamics of the Hokkaido-Sakhalin folded region. Moscow Nauka, 93p. Melnikov O.A., 2011. About dynamics and nature of Pugachevsky group the gaswaterclastic ("mud") volcanoes on Sakhalin according to visual observations and an orohydrography. Volcanology and Seismology, 6, 47-59. Melnikov O.A., Ershov V.V., Kim Chong Un, etc., 2008. About the mud spring activity dynamic of the gaswaterclastic ("mud") volcanoes and its connection with seismicity on the example of the Yuzhno-Sakhalinsky volcano (Sakhalin Island). Pacific Geology 27(5), 25-41. Melnikov O.A., Iliev A.Y., 1989. About new manifestations of mud volcanism on Sakhalin Island. Pacific geology 3, 42-48. Milkov, A.V., 2000. Worldwide distribution of submarine mud volcanoes and associated gas hydrates. Marine Geology 167, 29-42. Oreshkin V.N., Gordeev V.V., 1983. Geochemistry of cadmium and plumbum in suspension of the rivers of Black, Azov and Caspian Sea areas. Geochemistry, 4, 603-613. Petelin V.P., 1957. Mineralogy of sand-aleurite fractions in the Sea of Okhotsk marine sediments. Proceedings of Oceanology Institute of USSR Academy of Sciences, XXII. Prasolov E.M., 1990. Isotope geochemistry and origin of natural gases. St. Petersburg: Nedra, 283p. Shakirov R.B., 2016. Gasgeochemical fields of the marginal seas on the Far Eastern Region: distribution, origin, relations to the geological structures, gashydrates and seismo-tectonics. Dissertation of Doctor of Geological and Mineralogical Sciences (Dr.Sci.). POI FEB RAS, Vladivostok 459p. (In Russian). Shakirov R.B., Syrbu N.C., Obzhirov A.I., 2012. Isotope and gas-geochemical features of methane and carbon dioxide distribution on Sakhalin Island and adjacent shelf of the Okhotsk Sea. Bulletin of KRAESC Earth Sciences, 2(20), 100-113. Shnyukov E.V., et al., 1992. Mud volcanism of the Kerch and Tamansky region. Kiev, Naukova dumka, 200p. Siryk I.M., 1968. Oil and gas content of the east slopes of the West Sakhalin mountains. Moscow: Nauka, 8-14. Sorochinskaya A.V., et al., 2008. Geochemical and mineralogical features of mud volcanoes of Sakhalin Island. Bulletin of FEB RAS, 4, 58-65. Veselov О.V., Soinov V.V., 1997. Tektonosphere geodynamics of conjaction zone of the Pacific Ocean with Eurasia. Yuzhno Sakhalinsk: IMGG FEB RAS 4, 153-176. Veselov O.V., Volgin P.F., Lutaya L.M., 2012. Structure of the Pugachevsky mud-volcano sedimentary cover (Sakhalin Island) by geophysical modeling data. Pacific Geology, 31(6), 4-15. Vinogradov A.P., 1962. Average contents of chemical elements in the main types the igneous rocks. Geochemistry, 7, 555-571. Yakubov A.A., et al., 1980. Mud volcanism of the Soviet Union and its connection with oil-and-gas content. Baku, 165p. Zharov A.E., Mitrofanova L.I., Tuzov V.P., 2013. Stratigraphy of Cainozoic sedoiments of the Northern Sakhalin shelf. Stratigraphy, Geological correlation 21(5), 72-93.